2015
DOI: 10.1002/app.42951
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbranched polyglycerol/poly(acrylic acid) hydrogel for the efficient removal of methyl violet from aqueous solutions

Abstract: Hydrogels were synthesized from hyperbranched polyglycerol (HPG) and acrylic acid through free‐radical polymerization with HPG as the crosslinker. The HPG/poly(acrylic acid) (PAA) hydrogel could absorb cationic dyes in aqueous solutions because of the existence of a porous structure and the large numbers of hydroxyl and carboxylic groups. With methyl violet chosen as a model compound, the HPG/PAA hydrogel reached a maximum adsorption of 394.12 mg/g at a feed concentration of 1 g/L. The highest removal ratio of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 46 publications
3
6
0
Order By: Relevance
“…Therefore, the electrostatic interaction attraction between the hydrogel (COO − and NH) and the dye molecules (N + ) enhances the removal efficiency of the dye molecules. Similar results are reported in literature for MV adsorption by the hydrogel 42–44 …”
Section: Resultssupporting
confidence: 92%
“…Therefore, the electrostatic interaction attraction between the hydrogel (COO − and NH) and the dye molecules (N + ) enhances the removal efficiency of the dye molecules. Similar results are reported in literature for MV adsorption by the hydrogel 42–44 …”
Section: Resultssupporting
confidence: 92%
“…Besides the characteristic peaks from polyglycerol, it is observed a defined peak at 1718 cm -1 related to the C=O stretching of carbonyl groups of the PRE AA. Furthermore, at 1456 and 1407 cm -1 are found the asymmetric and symmetric COOstretching, respectively, of the carboxylate anion [39]. Similarly to the copolymer mentioned above, it is observed the C=O stretching at 1750 cm -1 indicating the incorporation of PRE LA segments to the polyglycerol backbone [40].…”
Section: Resultssupporting
confidence: 53%
“…27 Figure 4(c) shows the TGA curves of C-1, C-2, C-3, and C-4. 27 Figure 4(c) shows the TGA curves of C-1, C-2, C-3, and C-4.…”
Section: Thermal Performancesmentioning
confidence: 99%
“…The thermal stabilities of synthesized resins were investigated by TGA, and the results were used to determine the actual content of each polymer in the resins. 27 Figure 4 The 81.82 wt % weight loss in the temperature range of 320-520 8C was increasingly significant because of the rupture of the main-chain backbone and the destruction of the crosslinked network. 28 The differential curve for C-2 indicated that the weight-loss temperature of C-2 at 245.7 8C was extended compared with those of C-1, C-3, and C-4, as well as much higher than those of other resins.…”
Section: Thermal Performancesmentioning
confidence: 99%